CC-005 A confusing case of colitis. (23rd September 2015) - Kumar, M; Ravikumar, R; Hossain, J
Abstract : Introduction: The common causes of acute bloody diarrhoea include infective gastroenteritis, inflammatory bowel disease, pseudomembranous colitis and ischaemic colitis. We present a case of refractory colitis in an elderly patient who did not respond to conventional treatment. Methods: 75-year-old male patient presented with 2-day h/o bloody diarrhoea, vomiting and fever. Past medical history included diabetes and hypertension. Physical examination revealed mildly distended, non-tender, soft abdomen. Blood tests showed leucocytosis with neutrophilia and CRP 223. Stool culture was negative for clostridium toxin. Colonic obstruction and ischaemia were ruled out by CT scan. Sigmoidoscopy showed marked ulceration and cobblestone appearance with mucoid exudates in sigmoid colon suggesting IBD. Patient was commenced on corticosteroids. Histology showed crypt distortion and inflammatory changes, but H&E staining showed characteristic owls-eye inclusion bodies. Immunohistochemistry confirmed owls eye inclusion bodies suggesting acute CMV colitis. CMV IgG antibodies were positive and CMV viralload PCR was 60×100 000 indicating acute viraemia. Patient was treated with IV Ganciclovir for 2 weeks and corticosteroids were stopped. Repeat colonic biopsies were negative for CMV inclusion bodies, but endoscopic appearances remain unchanged. Patient developed toxic megacolon, peritonitis and died as patient was unfit for surgery. Results: In our patient, both serology and histology initially suggested a diagnosis of CMV colitis, although endoscopic appearances and histological features were indistinguishable from ulcerative colitis. Corticosteroids were stopped, as there was a risk of worsening CMV colitis due to immunosuppression by steroids. IV Ganciclovir did not improve symptoms suggesting ulcerative colitis as the cause of diarrhoea and CMV as an innocent bystander. Conclusion: Primary CMV colitis is rare in immunocompetent patients. Most cases of CMV colitis have been reported in refractory, steroid resistant ulcerative colitis or HIV patients.1 Treatment with IV Ganciclovir results in improvement of ulcerative colitis.2 Our case demonstrates that distinguishing primary CMV colitis from ulcerative colitis with latent CMV infection can be difficult in immunocompetent patients and initiating right treatment can be challenging.